The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1371/journal.pone.0075563
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Population Dynamics of Two Closely Related Species Differing in Ploidy Level

Abstract: BackgroundMany studies compare the population dynamics of single species within multiple habitat types, while much less is known about the differences in population dynamics in closely related species in the same habitat. Additionally, comparisons of the effect of habitat types and species are largely missing.Methodology and Principal FindingsWe estimated the importance of the habitat type and species for population dynamics of plants. Specifically, we compared the dynamics of two closely related species, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 77 publications
2
10
0
Order By: Relevance
“…High inter‐population differences in germination rates may have been further caused by some populations being favoured over others by local climate and soil in the common garden. In fact, Černá & Münzbergová () demonstrated that habitat conditions may be more important determinants of plant performance than plant cytotype. A diminished germination rate in the D1 and T5 populations might indeed have been caused by a less fertile soil used in the experiment (pseudogley and cambisol occur in the Ostrava basin and in Kozlovice, respectively; Weissmannová et al ., ) compared with the brown soil occurring in the White Carpathians (http://www.bilekarpaty.cz/strazci/img/mapy/pedologie.pdf), where these two populations originate.…”
Section: Discussionmentioning
confidence: 99%
“…High inter‐population differences in germination rates may have been further caused by some populations being favoured over others by local climate and soil in the common garden. In fact, Černá & Münzbergová () demonstrated that habitat conditions may be more important determinants of plant performance than plant cytotype. A diminished germination rate in the D1 and T5 populations might indeed have been caused by a less fertile soil used in the experiment (pseudogley and cambisol occur in the Ostrava basin and in Kozlovice, respectively; Weissmannová et al ., ) compared with the brown soil occurring in the White Carpathians (http://www.bilekarpaty.cz/strazci/img/mapy/pedologie.pdf), where these two populations originate.…”
Section: Discussionmentioning
confidence: 99%
“…However, results of other studies suggest that this ability is not universal among polyploid invaders ( Münzbergová 2007 a , b ; Černá and Münzbergová 2013 ; Godsoe et al . 2013 ), and in a few instances, diploids tolerated a wider range of ecological conditions than closely related polyploids ( Buggs and Pannell 2007 ; Černá and Münzbergová 2013 ). Studies comparing the ecological responses of diploid and polyploid congeners to contrasting environments are rare ( Soltis et al .…”
Section: Introductionmentioning
confidence: 89%
“…High variability within A. tridentata also includes frequent and widespread polyploidy (Richardson, Page, Bajgain, Sanderson, & Udall, ). As a genomic trait that can alter plant fitness, polyploidy is a key component of intraspecific variation in plant populations (Černá & Münzbergová, ). For at least some taxa, studies suggest higher drought tolerance in polyploids than diploids populations (e.g.…”
Section: Introductionmentioning
confidence: 99%